Synthesis of Cobalt Doped ZnO/Co₃O₄ heterostructures for Efficient methylene blue dye degradation application - Degefa Bekele (ASTU, 2025)
Catalysis research has turned its attention to improving optical and charge transfer materials by combining doping and interfacial engineering. Cobalt-doped ZnO/CoO (CZnO) heterostructures were created in order to accomplish an effective photocatalytic process for the breakdown of methylene blue dye. Successful cobalt incorporation and heterojunction development were confirmed by XRD analysis, which showed changes in diffraction peaks and the appearance of distinctive Co3O4 peaks.The crystallite sizes for pure ZnO and the doped heterostructure were detected as 26.3 nm and 10.7 nm, in the order given. High resolution TEM images showed sharp lattice patterns with d-spacings of 0.273 nm for ZnO and 0.241 nm for Co₃O₄, further verifying the interface formation. CZnO particles exhibited nanoscale dimensions ranging from 27 to 50 nm. Surface morphology analysis via FESEM and elemental mapping through EDX confirmed a uniform distribution of cobalt and the absence of impurities. UV-vis DRS technique indicated improved light absorption and a notable reduction in band gap energy upon cobalt doping, with indirect bandgaps of 3.05 eV for ZnO and 1.71 eV for CZnO. Photoluminescence (PL) spectra showed decreased emission intensity for CZnO, suggesting efficient charge separation at the heterojunction interface. The photocatalytic performance of CZnO showed a 4.5-fold increase in the degradation rate of methylene blue (k = 0.141 min⁻¹) compared to pure ZnO (k = 0.031 min⁻¹), attributed to enhanced optical and charge transport properties. The results confirm the potential of the porous CZnO heterostructure, prepared via a straightforward combustion method, for scalable photocatalytic applications.
Keywords: Extrinsic defect; intent contact; optical property; combustion; photocatalysis